Ciprofloxacin Decreases Collagen in Mouse Tympanic Membrane Fibroblasts. (July 2016) - Orobello, Nicklas C.; Dirain, Carolyn O.; Schultz, Gregory; Milne-Davies, Bailey A.; Ng, Maria R. A.; Antonelli, Patrick J.
Objectives: To determine how collagen production by tympanic membrane fibroblasts is affected by ciprofloxacin at levels found in eardrops. Study Design: Prospective, controlled, and blinded cell culture study. Setting: Academic tertiary medical center. Subjects: Cell culture of mouse fibroblasts. Methods: A primary fibroblast culture was established from mouse tympanic membranes. Fibroblasts were cultured until they were 75% confluent, then treated with dilute hydrochloric acid (control) or ciprofloxacin (0.01% or 0.3%) for 24 or 72 hours for Western blotting and for 24 or 48 hours for cytotoxicity assay. Cells were observed with phase-contrast microscope. Western blotting was performed for collagen type 1 α1 (collagen 1A1) and α-tubulin. Results: Fibroblasts treated with 0.01% and 0.3% ciprofloxacin for 24 hours had lower levels of collagen 1A1 ( P = .0005 and P < .0001, respectively) and α-tubulin (both P < .0001) than control fibroblasts. Collagen 1A1 and α-tubulin levels were lower in fibroblasts treated with 0.3% than with 0.01% ciprofloxacin ( P = .02 and P = .014). After 72 hours, 0.3% ciprofloxacin completely eliminated collagen 1A1 and α-tubulin ( P < .001). Cells treated with 0.01% ciprofloxacin for 72 hours also had lower collagen 1A1 ( P < .0001) and α-tubulin ( P = .005) as compared with the control. Seventy-two-hour incubation in 0.01% or 0.3% ciprofloxacin resulted in lower levels of collagen 1A1 ( P = .009 and P < .0001, respectively) and α-tubulin ( P = .007 and P < .0001, respectively) than 24-hour incubation. Cytotoxicity assay and phase-contrast microscopy mirrored these findings. Conclusions: Treatment of tympanic membrane fibroblasts with 0.3% ciprofloxacin, as found in eardrops, reduces fibroblast viability and collagen and α-tubulin protein levels. These findings could explain tympanic membrane healing problems associated with quinolone eardrops.